CALPHAD-assisted development of in-situ nanocrystallised melt-spun Co-Fe-B alloy with high Bs (1.57 T) - Stamenov, Plamen (My University, 2021)
A thermodynamics-based approach, Calculation of Phase Diagram (CALPHAD), combined with topological instability parameters are proposed and experimentally evaluated, in order to optimise in-situ nanocrystallisation of rapidly quenched CoFeB alloys and exploit their remarkable Bs = 1.57 T. The high Ms of the alloy is attributed to the precipitation of the metastable Co7Fe3 nanocrystalline phase dispersed heterogeneously in the amorphous matrix. High Ms of Co7Fe3 phase can also be inferred from the high hyperfine magnetic field of the Fe nuclei deduced from Mössbauer spectra. It is worth noting that the in-situ nanocrystallisation is a volume phenomenon, instead of surface crystallisation at the air-side of ribbons owning to lower cooling rates. We judge, based on nucleation theory, that the formation of the metastable phase is kinetically favoured, when compared to the equilibrium phases, hence promoting the high Ms, when compared with conventional Co-rich amorphous alloys. The local atomic order of nanocrystallised phase was confirmed by X-ray and electron diffraction techniques. Using Mössbauer spectroscopy and the extracted distribution of the hyperfine magnetic field, it is asserted that cobalt atoms form clusters, as they attract each other to form ordered structures, and boron atoms undergo only short-range ordering, likely due to covalent bond formation, governed by the size and electronegativity differences with the atoms in the amorphous matrix. We suggest the proposed CALPHAD-assisted design of nanostructured alloys, along with an in-situ nanocrystallisation, provides a practical scheme to develop novel functional alloys with the best possible balance of coercivity and saturation, exclusively aimed for a high-tech application.
PUBLISHED
Keywords: Calculation of Phase Diagram (CALPHAD); CoFeB alloys; Mössbauer spectra; Mössbauer studies; Rapid quenching; Soft magnetic properties; Nanocrystallisation; Nanostructured alloys; Alloy design; Amorphisation capability